Educational Leadership and Organizational Change in Oman: Toward an Interdisciplinary Transformation - Atef, Raed (Journal of Education and Learning Environments, 2025)
This study examines how integrated educational leadership can foster interdisciplinary collaboration and organizational agility in Omani educational institutions, in alignment with Oman Vision 2040. Using a qualitative approach based on secondary data analysis, the research synthesizes literature, policy documents, and institutional reports to propose a culturally grounded leadership framework. The model combines distributed, instructional, entrepreneurial, and culturally responsive leadership to address the complex demands of educational transformation. Findings indicate that distributed leadership supports shared decision-making and mobilizes expertise across institutional levels, while instructional leadership clarifies educational goals and nurtures effective learning environments. Entrepreneurial leadership encourages innovation through creativity and risk-taking, and culturally responsive leadership ensures alignment with Omani values and societal norms. Together, these dimensions form a synergistic framework that enhances interdisciplinarity, institutional adaptability, and alignment with national development priorities. Despite policy emphasis on interdisciplinary education, barriers such as limited university–industry collaboration and underdeveloped research capacity constrain agility and innovation. Based on these insights, the study recommends enhancing leadership development, improving research infrastructure, expanding digital capacity, and embedding leadership and interdisciplinarity criteria into accreditation standards. The study contributes conceptually by integrating diverse leadership theories into a context-sensitive model and provides actionable guidance for policymakers and educational leaders. Future research using primary data and regional comparisons is suggested to validate and refine the framework.